Gastrocnemius myocutaneous flap for prevention and treatment of osteomyelitis - Mohd Yusof, Nazri; Sulong, Ahmad Fadzli (2016)
Gastrocnemius myocutaneous flap has been used to cover a very large area of wound from the knee until distal third of the leg. The main problem with this flap is the donor site morbidity .the aim of this paper is to describe the surgical technique and the outcome related to the use of this to cover large wound in the leg. A series of 19 patients operated from 2002 til 2015 were reviewed retrospectively. there were 16 male and 3 female with the mean age of 25.2 (range 13-70). Nine wounds were located at the proximal tibia, 9 at midshaft and 1 around the knee with the mean size of 61.8 cm2 (range 30-180).. Ten were transposition flap while 9 were islanded. Fifteen donor site were skin frafted while 4 were able to close primarily. All except one flaps healed uneventfully or with minor dressing. One had to undergone below knee amputation because of persistence infection. Two patients had partial skin graft failure and the donor site which healed by dressing.One patient had extention lag due to ineficient quadricep mechanism. one had 10 degree knee contracture due to tibial plateu fractures. two patient had equinus secondary to underlying sciatic nerve injury. gastrocnemius myocutaneous flap is a good option for closure of large defect around the knee till the distal third of leg. Primary wound closure is possible for islanded gastrocnemius myocutaneous flap may reduce the donor site morbidity. aggressive post operative physiotherapy may reduce the knee and ankle contracture.